THEORETICAL AND METHODOLOGICAL SUPPORT FOR THE PROCESS OF STRUCTURAL TRANSFORMATION OF THE ECONOMY (Development Service Industry Management, 2025)
The article is devoted to the study of the theoretical and methodological foundations of the structural transformation of the economy as a strategic resource for ensuring sustainable development of the national economy in the context of global competition, digitalization, and technological evolution. The purpose of the article is to substantiate and improve the theoretical and methodological framework for the process of structural transformation of the economy aimed at achieving balanced socio-economic development, enhancing the competitiveness of the national economy, and adapting it to current global and internal challenges.The study explores the evolution of conceptual foundations of the economic structure and defines its role in ensuring economic stability, competitiveness, and social adaptability. A three-component approach to structural transformation is substantiated, which includes sectoral changes, transformation of economic behavior, and modernization of state policy. A conceptual model of structural transformation is proposed, which, in comparison with existing models, is based on a combination of evolutionary, neoclassical, and modernization approaches. It is revealed that successful structural transformation involves the transition to an innovation-driven economic model, the development of high value-added sectors, digitalization, and the renewal of the institutional framework.The main conditions for the effectiveness of transformational processes are identified, including the coherence of sectoral, regional, and innovation policy; the presence of effective strategic planning mechanisms; the development of human capital; and the provision of social protection during the transition period. Institutional support is examined as a key factor determining the stability and irreversibility of structural changes. At the macro level, structural transformation is manifested in changes in the structure of GDP, exports, investments, and tax revenues, while at the micro level, it is seen in the transformation of organizational models of enterprises and the implementation of digital platforms.Overall, the study showed that structural transformation should be considered a complex, multi-level process that encompasses economic, social, technological, and institutional changes. The theoretical understanding of this phenomenon enables the development of effective economic policy mechanisms focused on adaptability, inclusiveness, and sustainable development.
Keywords: structural transformation; economic structure; innovation-driven development; state policy; institutional support; sectoral modernization; sustainable development